Playful poetics of V.V. Nabokov's story title 'Tyrants Destroyed' - G.Yu. Maltseva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper provides a detailed analysis of the features of the title of V.V. Nabokov's story “Tyrants Destroyed” as an example of the iconic sign in the light of the theory of language-game poetics. The study is highly relevant, because it offers a new way to describe the features of the title text based on language game. By considering the title as an iconic sign we focused on its semantic, syntactic, and pragmatic features. The title of the story under study is as an autosemantic element and an iconic sign that will be deciphered in the text, but carries important prior information. To describe the peculiarities of the title, we used the theory introduced by Ch. Morris on the triple essence of the sign. According to this theory, the title was considered as an iconic sign: its semantics, syntactics, and pragmatics were described. The semantic and syntactic analysis of the title revealed its bipolar structure, which is generally expressed as “counteraction to action”. With the help of the pragmatic analysis, the role of inclusions in the text in the form of multiple repetition of the name Hamlet was determined. Based on the data obtained by the semantic and syntactic analysis, we concluded that the allusion emphasizes the playful nature of the text and refers to the title, which acquires an additional connotation. The introduction of the precedent name Hamlet not only helps to decode the semantic content of the title, but also reveals V.V. Nabokov's critical point of view on another text – the tragedy of “Hamlet” by W. Shakespeare.